Bibliografia Ladina Bibliografie des ladinischen Schrifttums 1/Bibliografia degli scritti in ladino 1 - Videsott, Paul (Scripta Ladina Brixinensia, 2014)
The first volume of the Bibliografia Ladina covers the entire Ladin Literature from the beginnings up to 1945. A total of 1072 entries, including manuscripts and parts of text, is ordered by authors and contains additional information regarding the date of their origin, the place and date of publication, the publication history, the idiom as well as the digital availability of the individual texts. Several indices (e.g. of the incipits) are included. Thus, this bibliography can either be used as a supplement to the first volume of the Geschichte der ladinischen Literatur (The History of Ladin Literature - Scripta Ladina Brixinensia III/1) or as an independent research tool.